Support for an Explanation of the Guidance Effect in Motor Skill Learning - Anderson, David I. (2005)
The authors investigated whether the knowledge of results (KR) schedule influences the extent to which intrinsic feedback is noticed and used. Fifty-six participants received KR that was either delayed over 2 trials (Delay-2) or provided directly after each trial (Delay-0) during 160 trials of an unfamiliar aiming task. No-KR retention tests were given after 80 trials and 1 min and 24 hr after the end of acquisition. After retention, all participants were questioned about their use of intrinsic feedback during practice and whether those sources changed as a function of practice. The Delay-2 group performed significantly less accurately on the 1st and last blocks of acquisition trials but showed a significantly smaller performance decline from acquisition to retention. Moreover, the Delay-2 group noticed and used a greater variety of intrinsic feedback sources and its members were more likely to report that their usage changed with practice.